Verification of Bounded Rationality Models of Price Dispersion on an Online Marketplace Data (Advances in Systems Science and Applications, 2023)
We explore how well the models of bounded rationality explain price dispersion observed in Internet price-comparison sites.This paper considers three hypotheses about the strategic origin of price dispersion in homogeneous product online sales. Two of them are $ε$-equilibrium and quantal-response equilibrium (QRE) in a pure Bertrand setting, they involve the bounded rationality of sellers. The third hypothesis introduces the fraction of loyal consumers into the model and assumes the sellers are rational. These behavioral models earlier were proposed in the literature as possible explanations of high price dispersion in online markets. They were supported by experimental lab data, but not tested on real prices. We test the hypotheses on real data for 30 models of household appliances collected from the largest Russian online marketplace Market.Yandex.ru, which organizes e-competition in the closest to the Bertrand setting way. We found no support for $ε$-equilibrium hypothesis and only limited support for loyal consumer hypothesis. QRE showed the best performance on the data. For most of the products it predicts central tendency, i.e. the mean and the median, remarkably well. The shape of the observed price distributions is explained accurately enough in comparison with the two other hypotheses and random behavior.